Integration of Postcoordination Content into a Clinical Interface Terminology to Support Administrative Coding - Rose, Eric; Rube, Steven; Kanter, Andrew S.; Cardwell, Matthew; Naeymi-Rad, Frank (Applied Clinical Informatics, 2019)
Background Clinical interface terminologies (CITs) consist of terms designed for clinical documentation and, through mappings to standardized vocabularies, to support secondary uses of patient data, including clinical decision support, quality measurement, and billing for health care services. The latter purpose requires maps to administrative coding systems, such as the International Classification of Diseases, 10th Revision, Clinical Modification (ICD-10-CM), for diagnoses in the United States.Objectives The transition from ICD-9-CM to ICD-10-CM posed a challenge to CIT users due to the substantially increased details in ICD-10-CM. To address this, we developed a content layer within a CIT that provides postcoordination prompts for the details required for accurate ICD-10-CM coding.Methods We developed content to support prompting for and capture of additional information specified by the user in a single, clinically relevant term that is added to the patient's record, and whose mapping to other coding systems (like Systematized Nomenclature of Medicine—Clinical Terms [SNOMED CT]) reflects the details added during postcoordination. We worked with clinical information system developers to incorporate this into user interfaces, and with end-users to refine the design.Results While the prompts were designed around the precoordinated elements implicit in ICD-10-CM, irregularities in ICD-10-CM required some additional design measures, such as providing postcoordination options that interpolate gaps in ICD-10-CM to avoid user confusion. The system we describe has been implemented by ∼30,000 health care provider organizations, with content that covers the vast majority of encounter diagnoses. User feedback has been largely positive, though concerns have been raised about expanding postcoordination content beyond that required for ICD-10-CM coding.Conclusion We have demonstrated the design and development of what, to our knowledge, is the first system that uses postcoordination to capture ICD-10-CM-relevant details in a CIT while also reflecting the details added by the user in maps to other vocabularies.
Keywords: clinical information systems; interfaces; ICD-10; standards